Динаміка показників окислювальної модифікації білків у хворих на акантолітичну пухирчатку - Літвінов, Володимир Анатолійович; Федотов, Валерій Павлович; Литвинов, Владимир Анатольевич; Федотов, В. П.; Litvinov, V. A.; Fedotov, V. P. (My University, 2017)
Цель работы: Повысить значимость определения степени для характеристики эндотоксических процессов у больных акантолитической пузырчаткой в динамике лечения их глюкокортикостероидами. Материал и методы исследования: Изучен уровень ВНСММ у 12 больных акантолитической пузырчаткой до и после лечения их глюкокортикостероидами. У всех больных диагностирована вульгарная пузырчатка, мужчин - 3, женщин - 9 в возрасте 57-72 лет. Контрольную группу составляли 30 практически здоровых лиц. Методика: Оценивали по показателям окислительной модификации белков по методике В. На1^еИ. Результаты и обсуждение. У больных акантолитической пузырчаткой отмечен рост в плазме крови веществ низкой и средней молекулярной массой, как показатель наличия у них эндогенной интоксикации с повышением уровня общей окислительной модификации белков. Эндогенная интоксикация резко растет после лечения больных на фоне терапевтического приема глюкокортикостероидов на протяжении 1,5-2 месяцев. Отмечена прямая корреляция между уровнем ВНСММ и окислительной модификации белков, что свидетельствует о повышении уровня окисляемости белковых молекул, что 'Связано с деструктивными процессами эндотоксинами. Выводы: У больных акантолитической пузырчаткой выявлена эндогенная интоксикация, увеличение АФГ и КМГ, уровень которых резко увеличивался после лечения их глюкокортикостероидами. Эндогенная интоксикация установлена на длиннах волн 254нм и 272нм. Установлена прямая корреляция между уровнем ВНСММ и окислительной модификации белков, что обусловлено деструктивными процессами эндотоксинами. Objective: to increase the importance of determining the degree to characterize endotoxic processes in patients with acantholytic pemphigus in the dynamics of treatment with glucocorticosteroids. Material and methods of investigation: The LMMWS level was studied in 12 patients with acantholytic pemphigus before and rter treatment with glucocorticosteroids. All patients diagnosed with pemphigus vulgaris: 3 men and 9 women aged 57-72 years, "he control group consisted of 30 practically healthy persons. Methods: was the evaluation was performed according to indexes of oxidative modification of proteins by the method of V. -fafliwell. The results and discussion. Patients with acantholytic pemphigus marked increase in plasma blood substances of low and -edium molecular weight as an indicator of the presence of their endogenous intoxication with higher levels of total oxidative —edification of proteins. Endogenous intoxication significantly increases after treatment of patients on background therapy taking xacosteroids for 1.5-2 months. A direct correlation between the level of LMMWS and oxidative modification of proteins was noted, «fitch indicated an increased level of oxidation of protein molecules, which is associated with destructive processes by endotoxins. Conclusions: endogenous intoxication, increase of AFG and KMG were identified in patients with acantholytic pemphigus, the eve! of which sharply increased after treatment with glucocorticosteroids. Endogenous intoxication was fixed at wavelengths 254nm and 272nm. There was a direct correlation between the level of LMMWS and oxidative modification of proteins, due to the Destructive processes by endotoxins.
Keywords: ендогенна інтоксикація; глюкокортикостероїди; білкі; деструкція; молекулярна маса; альфадегідфенілгідразона; кетондинітрофенілгідразона; acantholytic pemphigus; endogenous intoxication; glucocorticoids; proteins; destruction; molecular weight; alphadehydphenylhydrason; cetondynitrophenylhydrason